Analysis of the implementation of the SMED methodology to reduce machine setup times and die change in the food industry: a literature review - Barrantes Geronimo, Mayra Alejandra (2023)
This research seeks to spread the use of the Single minute exchange of die (SMED) tool. According to the literature reviewed, there are few investigations where this tool is applied in companies in the food sector. The objective of the study is to conduct an analysis of the research carried out on the implementation of the SMED tool in the food industry. A systematic review of the literature was implemented, 3 categories and 7 study subcategories were formed to analyze 30 articles published between 2015 and 2021. It was found that 64% of the articles were concentrated between 2017 and 2019, and that 43% were made in Latin America. Also, it was found that work methods are the main cause that affects the changeover time and 67% of the articles reviewed mention the increase in productivity as the main benefit. The principal obstacle to the implementation of this methodology is the lack of staff training. The major limitation found in this research is that the cost reduction calculations mentioned are not detailed. For future research, it is recommended to detail the quantification of cost reduction after SMED implementation.